Calvinistic baptists in Jamaica? : a historical-theological study of the relationship between the theology and work of five pioneering missionaries in Jamaica - Campbell, Sheldon (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.